2023
DOI: 10.1051/0004-6361/202346384
|View full text |Cite
|
Sign up to set email alerts
|

Solar energetic particle event onsets at different heliolongitudes: The effect of turbulence in Parker spiral geometry

Abstract: Context. Solar energetic particles (SEPs), accelerated during solar eruptions, are observed to rapidly reach a wide heliolongitudinal range in the interplanetary space. Turbulence-associated SEP propagation across the mean Parker spiral direction has been suggested to contribute to this phenomenon. Aims. We study SEP propagation in turbulent magnetic fields to evaluate SEP spatial distribution in the heliosphere, their path lengths, and the overall evolution of SEP intensities at 1 au. Methods. We use full-orb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…Their work confirms that the peak field line path length is reasonably well described by the simple expression of Chhiber et al (2021a), which corresponds to Equation (9) in the present work. Their corresponding results for 100 MeV proton path lengths (Laitinen et al 2023b) are also comparable to the results in our Table 1 for 1 MeV protons with b/B 0 = 0.75, when accounting for the 0.17 au path length difference along the mean field lines.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Their work confirms that the peak field line path length is reasonably well described by the simple expression of Chhiber et al (2021a), which corresponds to Equation (9) in the present work. Their corresponding results for 100 MeV proton path lengths (Laitinen et al 2023b) are also comparable to the results in our Table 1 for 1 MeV protons with b/B 0 = 0.75, when accounting for the 0.17 au path length difference along the mean field lines.…”
Section: Discussionsupporting
confidence: 86%
“…But farther from the Sun, as this process weakens, pitch-angle scattering drives the distribution to larger values of the pitch angle (Ruffolo & Khumlumlert 1995). Simulated path length distributions have also been presented for field lines by Laitinen et al (2023a) and Li & Bian (2023) and for energetic particles by Laitinen et al (2023b). Various studies recognize that while nominal path lengths are computed relative to a typical Parker spiral magnetic field (Parker 1958), it is worth noting that inside an interplanetary magnetic flux rope (e.g., inside an interplanetary coronal mass ejection), path lengths of field lines and particles can be much longer (e.g., Larson et al 1997;Wimmer-Schweingruber et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…For a fixed source this usually implies more efficient particle transport toward the west of the best-connected HMF line, as these particles are transported away from the Sun, leading to asymmetrical distributions in terms of longitude. In this context, see also the recent simulations of Laitinen et al (2023). (2017), and Bruno & Richardson (2021).…”
Section: On the Geometry Of Perpendicular Diffusionmentioning
confidence: 85%
“…This can be related to the fact that more complex ARs generate stronger flares (in terms of their soft X-ray class) that statistically result in faster and wider CMEs. The CME width was recently indicated to be an important parameter for SEP forecasting (Torres et al 2022); on the other hand, the recent work by Laitinen et al (2023) indicated that SEPs can arrive from a wide range of longitudes, even without a wide particle source. We also notice that the AR records close to the western limb and behind it are extrapolated records, and for them the AR class is assumed to be unchanged from the last reliable observations.…”
Section: Hale Classificationmentioning
confidence: 99%